Gondolatok a területfejlesztés hatékonyságáról - Pászti-Tóth, Erzsébet (Közép-Európai Közlemények, 2011)
The aim of the study, titled „Thoughts about the efficiency of settlement)improvement” is to show connections and efficiency in domestic region-improvement/settlement-improvement, which appear in practice, emphasizing region politics, configuration, regulation background, organizational-institutional “system” and resource “system”, especially in connection to the local (settlement) development. Several areas of this question became the means of party politics which conceals puzzling relations and connections in some places. Therefore this study is only for an overview, showing the developed situation concerning this field, which may be a starting state according to region-improvement/settlement-improvement. For this reason I am searching for the answer for the following questions: In the practice of settlement-improvement to what extent do local interests, initiatives coming from below, principles of region)improvement – taken over from the EU -(programming, subsidiarity, partnership, addition, concentration) succeed? As well as: in what extent do region-improvement, configuration, region politics, the institutional and resource systems operated for this purpose serve the social-economical-environmental development, and what lessons might be drawn concerning settlement-improvement/region-improvement? During the analysis Faragó László’s “The conceptual system of region)improvement” serves as a basis. There is no chance for the full exposition of this topic here; therefore I confine myself to point out some lessons which might be drawn in connection to the development of the settlements’ current social)economical situation, under the aegis of the happenings of settlement-improvement/ region-improvement. The research divides into three chapters: –The period after the change of regime, -The period between 1996 and our joining to the European Union (May 1, 2004), –The period after joining the European Union. In every chapter I look through the region politics, the local regulation, the organizational and institutional systems; possibilities and anomalies on intermediate level and on the levels of cities (having county rights), small regions and settlements; sources and the practice of planning in the system of resources, and the dominant effects. Finally I say a couple of words about the necessity of the bottom)up building’s adoption in region) development.